2022
DOI: 10.1021/acsmedchemlett.2c00446
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Coumarin-Based MEK1/2 PROTAC Effective in Human Cancer Cells

Abstract: The RAF/MEK/ERK pathway is a crucial signal path which is closely associated with the proliferation, differentiation, and apoptosis of tumors. MEK1/2 is a key kinase target in the pathway, with ERK1/2 acting as the main substrate of it. Despite the rapid development of MEK1/2 inhibitors, acquired resistance still happens and remains a significant problem. Most of the inhibitors possess a similar diarylamine scaffold. Here we designed and synthesized a series of MEK1/2 degraders based on a coumarin derivative w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The use of DCC instead of EDC·HCl for the synthesis of 2F[4] resulted in contamination of the product with urea byproducts, which were difficult to remove. The requisite ditosylates 4[ n ] were prepared according to a general procedure 51 and full procedures and analytical data are listed in the ESI †…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of DCC instead of EDC·HCl for the synthesis of 2F[4] resulted in contamination of the product with urea byproducts, which were difficult to remove. The requisite ditosylates 4[ n ] were prepared according to a general procedure 51 and full procedures and analytical data are listed in the ESI †…”
Section: Resultsmentioning
confidence: 99%
“…Dalton Transactions cedure 51 and full procedures and analytical data are listed in the ESI. † The pro-mesogenic ionic additive S2 [Li] was prepared as shown in Scheme 2.…”
Section: Papermentioning
confidence: 99%
“…Even if several MEK1/2 inhibitors were reported, acquired resistance remains a significant problem. Xu and co-workers designed and synthesized a series of coumarin-based MEK1/2 PROTAC MEK1/2 degraders based on a coumarin derivative which was a potent non-diarylamine allosteric MEK1/2 inhibitor effective in human cancer cells ( Wang et al, 2023 ). 216 is the most promising derivative showing a DC 50 values of 0.3 and 0.2 μM in MEK1 and MEK2 degradation, respectively.…”
Section: Biological Applications Of Coumarin Derivativesmentioning
confidence: 99%
“…Affected by upstream protein signals, signals can be transferred from the cytoplasm to the nucleus, such as RAS, [30] RAF, [31] MEK. [32] Furthermore, it mediates the transcriptional activation of downstream proteins and participates in cell proliferation and differentiation, senescence and apoptosis, [33] such as Elk-1, [34] ATF [35] , and Ap-1. [36] Liu [37] observed the changes of glomeruli and renal interstitium by increasing ERK1/2 phosphorylation in the HN rat model, and found that the pharmacological targeting of ERK2/1 can alleviate HN by inhibiting TGF-βsignal transduction, reducing inflammatory response and inhibiting molecular processes associated with elevated serum UA levels in the body.…”
Section: Extracellular Regulated Protein Kinase Signal Pathwaymentioning
confidence: 99%